(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
A simple, sensitive and accurate visible spectrophotometric method has been developed for the assay of mifepristone. The method is based on the colour reaction between Ce (IV) and mifepristone in the pH range 1.0-5.0.The golden yellow coloured complex is exploited for the development of a visible spectrophotometric procedure for the determination of mifepristone. The absorption spectrum of the complex shows maximum absorbance at 430nm at pH 2.0. Beer’s law is obeyed in the range 1.5-30.0 µg/ml of mifepristone. The molar absorptivity and sandell’s sensitivity are 1.714×104 l mol-1 cm-1 and 0.0251µg cm-2 respectively. The standard deviation of the method for ten determinations of 10 µg/ml mifepristone is 0.0013. The correlation coefficient () of the experimental data of the calibration plot is 0.9999. The proposed spectrophotometric method was validated according to ICH specifications. The validation parameters such as, linearity, accuracy, precision, LOD, LOQ and ruggedness were studied. The method for the quantitative assay of mifepristone was successfully applied for its assay in pharmaceutical formulations.